Quality of Life in The Community of Women with Polycystic Ovary Syndrome (PCOS): A Phenomenology Study - Istiqomah, Neina Qonita; Abidin, Zainal; Candoruk, Agit (Psympathic : Jurnal Ilmiah Psikologi, 2023)
Polycystic Ovary Syndrome (PCOS) is a hormonal, endocrine, and metabolic disorder in women of reproductive age. This is characterized by symptoms such as hirsutism, menstrual disorders and infertility, affecting almost 20% of women. In this context, the syndrome affects the physical and psychological disorders of women. Conditions that predominate in PCOS women cause depression and affect their quality of life. Using a phenomenological approach, in-depth interviews were conducted to determine quality of life in six PCOS women. The participants were recruited using purposive sampling from PCOS Fighter Indonesia community in the Bandung area. Furthermore, three themes were developed from the analysis, namely positive thinking, healthy behavior and social support. This resarch showed the favorable facets of the experiences of women coping with PCOS and showed the important role of the community in offering support to individuals affected by the syndrome. The identified themes emanated from interviews exploring quality of life among women with PCOS, providing insights into their daily lives and the challenges posed by the symptoms.